Vitamin C promotes wound healing through novel pleiotropic mechanisms. Issue 4 (20th August 2015) - Mohammed, Bassem M; Fisher, Bernard J; Kraskauskas, Donatas; Ward, Susan; Wayne, Jennifer S; Brophy, Donald F; Fowler, Alpha A; Yager, Dorne R; Natarajan, Ramesh
Abstract: Vitamin C (VitC) or ascorbic acid (AscA), a cofactor for collagen synthesis and a primary antioxidant, is rapidly consumed post‐wounding. Parenteral VitC administration suppresses pro‐inflammatory responses while promoting anti‐inflammatory and pro‐resolution effects in human/murine sepsis. We hypothesised that VitC could promote wound healing by altering the inflammatory, proliferative and remodelling phases of wound healing. Mice unable to synthesise VitC (Gulo −/− ) were used in this study. VitC was provided in the water ( sufficient ), withheld from another group ( deficient ) and supplemented by daily intra‐peritoneal infusion (200 mg/kg, deficient + AscA ) in a third group. Full thickness excisional wounds (6 mm) were created and tissue collected on days 7 and 14 for histology, quantitative polymerase chain reaction (qPCR) and Western blotting. Human neonatal dermal fibroblasts (HnDFs) were used to assess effects of In conclusion, VitC favorably on proliferation. Histological analysis showed improved wound matrix deposition and organisation in sufficient and deficient + AscA mice. Wounds from VitC sufficient and deficient + AscA mice had reduced expression of pro‐inflammatory mediators and higher expression of wound healing mediators. Supplementation of HnDF with AscA induced the expression of self‐renewal genes and promoted fibroblast proliferation. VitC favourably impacts the spatiotemporal expression of transcripts associated with early resolution of inflammation and tissue remodelling.